Pencalonan Mantan Narapidana sebagai Anggota Legislatif Perspektif Fikih Siyasah - Musyafiatun, Musyafiatun (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This article focuses on the Islamic political jurisprudence perspective against the decision of the Constitutional Court (MK) No. 4/PUU-VII/2009 on the nomination of an ex of a prisoner as a legislator. MKâs decision allows the ex of a prisoner to become a legislator, DPD, and local leader with certain conditions. The basic of the consideration is that the Constitutional Court has the authority to examine, hear, and decide the decision No. 4/PUU-VII/2009. In addition, the applicant also has no legal status in this respect (legal standing) and consideration of the principal arguments of the applicantâs request. MKâs decision No. 4/PUU-VII/2009 has juridical implication on article 12 letter g and article 50 paragraph (1) letter g of Law No. 10/2008 and article 58 letter f of Law No. 12/2008 as well as the political implications on the opportunities for the ex of a prisoner to hold a public office. Based on the Islamic political jurisprudence perspective, MKâs decision No. 4/PUU-VII/2009, which permitted the ex of a prisoner as a legislator, DPD and local leader with certain conditions, is in line with the concept of constitutional politics that includes the rights of the people. It is because the ex of a prisoner is also a member of the community whose rights should be protected if he or she repents.Keywords: Nominations, prisoner, members of the legislature.